Myeloid-related proteins 8/14 failed to act as theragnostic biomarker in axial spondyloarthritis patients on combination disease-modifying anti-rheumatic drugs therapy - Arvind Ganapati; Jayakanthan Kabeerdoss; Mahasampath Gowri; Belavendra Antonisamy; Debashish Danda (Indian Journal of Rheumatology)
Background: Reports signifying the utility of myeloid-related proteins (MRP) 8/14 in axial spondyloarthritis (AxSpA) as a theragnostic biomarker are scarce. Objectives: Evaluating the utility of serum MRP 8/14 (baseline levels and change from baseline to 3 months) in AxSpA as a predictor of Assessment of SpondyloArthritis International Society (ASAS) 20 response at 6 months post combination disease-modifying anti-rheumatic drugs (DMARD) therapy. Methods: Serum MRP 8/14 was assayed using enzyme-linked immunosorbent assay platforms (R&D systems, USA) at baseline in 83 AxSpA patients satisfying ASAS 2009 criteria meeting the predefined eligibility criteria; treated with a combination of methotrexate, sulfasalazine at optimum tolerated doses with on-demand nonsteroidal anti-inflammatory agents and 30 healthy age-matched controls. Repeat measurement was done at 3 months in 60 patients. Results: Median MRP 8/14 levels in AxSpA patients was 3.00 (3.96) μg/ml compared to 2.3 (3.29) μg/ml in controls (P = 0.2). Median baseline MRP 8/14 levels in ASAS 20 responders at 6 months (n = 36) was 3.6 (4.1) μg/ml compared to 2.4 (4.8) μg/ml in nonresponders (n = 35) (P = 0.4). Median △ (baseline to 3 months) MRP 8/14 levels in ASAS 20 responders at 6 months (n = 33) was – 1 (−2.7) μg/ml compared to − 0.2 (−3.8) μg/ml for nonresponders (n = 27) (P = 0.5). Among the 83 patients with 138 disease activity assessments at baseline and 3 months post therapy, median MRP 8/14 in active disease (bath ankylosing spondylitis disease activity index [BASDAI] ≥4) (n = 112) was 2.2 (3.8) μg/ml, compared to 2 (2.3) μg/ml (P = 0.5) in inactive disease (BASDAI < 4) (n = 26). Conclusion: Serum MRP 8/14 did not serve as a theragnostic biomarker in our cohort of AxSpA patients treated with combination DMARDs and on-demand NSAIDs.